Study of efficacy of epidural methylprednisolone acetate and triamcinolone acetate for treatment of low back pain and radiculopathy - Pahuja, Heena D.; Vyawahare, Kiran R.; Dhumane, Pradeep G. (International Journal of Advances in Medicine, 2019)
Background: Epidural steroids have been proven to be one of the most effective non-operative managements of back pain. The present study entailed evaluation of the efficacy of epidural methylprednisolone acetate and triamcinolone acetate for treatment of low back pain and radiculopathy. Methods: The two groups of 25 participants, formed on the basis of the injectable epidural steroid used {80mg of methylprednisolone acetate (group 1) or 40mg of triamcinolone acetate (group 2)}, were enrolled after following due selection criteria. After detailed history taking, examination and requisite investigations, 15 ml volume of the drug was injected epidurally with the patient lying in lateral position. The patients were followed-up at 3 weeks, 6 weeks and 3 months and pain assessment and percentage of pain relief was noted in comparison with the level of pain before epidural injection. Sleep quality, activity score, days in bed, analgesic requirement, complications and requirement of surgical intervention were all assessed at each follow-up. Results: The mean pain score was significantly less in group 1 after 6 weeks and 3 months period, with 60% in group 1 having “good” pain relief, while 69.56% amongst group 2 participants reported “fair” pain relief. Eighty four percent group 1 participants required 2 injections, while 64% participants in group 2 required 3 injections. There was overall improvement in the activity score, quality of sleep and decrease in bed rest and analgesic requirement. Conclusions: Epidural steroid therapy is highly efficacious and methylprednisolone acetate is more effective than triamcinolone acetate; with negligible complications.